The acoustic efforts of the Medieval Arab philosophers: brethren of purity as a model - Ahmed Mahmoud, Ragheb Ahmed; , (Scholink, 2015)
This study discusses the acoustic efforts of the Medieval Arab philosophers and thinkers, and explain specifically the efforts of Brethren of Purity (ikhwãn al-safã) also The Brethren of Sincerity). They were a famous secret society of Muslim philosophers in Basra, Iraq, in 4th century HD/8th century CE. The structure of this mysterious organization and the identities of its members have never been clear. This study is an overview of the reality and the actuality of the vocal acoustic research which the Arab thinkers produced. It also will discusses the efforts of Al-Safa brothers community in the Arab Acoustic field, who presented a logical definition of the linguistic sound, then started to categorize the sound according to the meaning, quantity and quality, determined the sounds articulation and the ways of its production, then they made a great analysis on the ways of analyzing it based on all the qualitative and quantitative levels, and highlighted the semantic aspects and the ways of recognizing and perceiving the sounds.